Analysis Of Factors Related To Delay Time of Ischaemic Stroke Patients at dr. R.Koesma Hospital, Tuban Regency - Henry Sudiyanto; Sudigdo Dwi Prasetyo; Arief Fardiansyah; Eka Diah Kartiningrum (CV Media Inti Teknologi, 2025)
Background of study: Delay time in arrival of ischemic stroke patients to the hospital is a special concern because the